Managerial Influence Of School Principals On Teacher Competency In MAN 1 Kediri City - Wahib, Abd. (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The aim of this research is to determine the managerial influence of school principals on teacher performance in MAN 1 Kediri City. The approach in this research is quantitative. The type of research used in this research is associative research. The population is the total number of MAN 1 Kediri City teachers, namely 83 teachers who are also the research sample. The data collection techniques are questionnaires and documentation. Data analysis used multiple linear regression. The results of the research are that there is a significant influence of conceptual skills on teacher competency in MAN 1 Kediri City, there is a significant influence of technical skills on teacher competency in MAN 1 Kediri City, there is a significant influence of Social Skills on competency teachers at MAN 1 Kediri City, there is a significant influence jointly between conceptual skills, technical skills and social skills on the competence of teachers at MAN 1 Kediri City.